Implementing Full Spatial Coverage in NOAA's Global Temperature Analysis. Issue 4 (21st February 2021) - Vose, R. S.; Huang, B.; Yin, X.; Arndt, D.; Easterling, D. R.; Lawrimore, J. H.; Menne, M. J.; Sanchez‐Lugo, A.; Zhang, H. M.
Abstract: The National Oceanic and Atmospheric Administration (NOAA) maintains an operational analysis for monitoring trends in global surface temperature. Because of limited polar coverage, the analysis does not fully capture the rapid warming in the Arctic over recent decades. Given the impact of coverage biases on trend assessments, we introduce a new analysis that is spatially complete for 1850–2018. The new analysis uses air temperature data in the Arctic Ocean and applies climate reanalysis fields in spatial interpolation. Both the operational analysis and the new analysis show statistically significant warming across the globe and the Arctic for all periods examined. The analyses have comparable global trends, but the new analysis exhibits significantly more warming in the Arctic since 1980 (0.598°C dec −1 vs. 0.478°C dec −1 ), and its trend falls outside the 95% confidence interval of its operational counterpart. Trend differences primarily result from coverage gaps in the operational analysis. Plain Language Summary: NOAA provides a suite of climate services to government, business, academia, and the public to support informed decision‐making. Among these services is the State of the Climate report, which is a collection of monthly summaries recapping climate‐related occurrences across the globe. This report relies heavily upon NOAA's global surface temperature data set to depict recent monthly conditions and long‐term changes. Our research introduces a new edition of this flagship data set that is based upon additional temperature data and improved scientific methods. The new data set extends back to 1850 and has complete coverage of all land and ocean areas for the first time. These improvements are particularly important in the Arctic, which has warmed more rapidly than the rest of the planet in recent decades, and the new data set likewise has larger trends than its predecessor in that part of the world. The introduction of this new data set is consistent with the NOAA practice of periodically developing improved versions of its foundational datasets, the goal being to ensure the best possible representation of historical conditions across the globe. The results of this study suggest that the new data set can substantially contribute to future NOAA monitoring and assessment activities. Key Points: NOAA's global surface temperature analysis has limited polar coverage, resulting in a small cold bias in recent decades We create a spatially complete analysis for 1850–2018 using Arctic air temperatures and climate reanalysis fields Full coverage has a slight impact on global trends, but it significantly increases warming rates in the Arctic since at least the 1980s